2007
DOI: 10.1038/sj.onc.1210529
|View full text |Cite
|
Sign up to set email alerts
|

Frequent activating FGFR2 mutations in endometrial carcinomas parallel germline mutations associated with craniosynostosis and skeletal dysplasia syndromes

Abstract: Endometrial carcinoma is the most common gynecological malignancy in the United States. Although most women present with early disease confined to the uterus, the majority of persistent or recurrent tumors are refractory to current chemotherapies. We have identified a total of 11 different FGFR2 mutations in 3/10 (30%) of endometrial cell lines and 19/187 (10%) of primary uterine tumors. Mutations were seen primarily in tumors of the endometrioid histologic subtype (18/115 cases investigated, 16%). The majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(239 citation statements)
references
References 19 publications
7
230
0
2
Order By: Relevance
“…The frequency of FGFR2 mutations in this series (6.45%) is a little bit lower than that of previous series (10-12%). [13][14][15] However, the number of cases tested for FGFR2 mutations is smaller than that of other series. It is worth mentioning that our series has the additional value that the cases had been previously tested for microsatellite instability, as well as mutations of KRAS, PTEN, PIK3CA and CTNNB1.…”
Section: Fgfr2 Mutationsmentioning
confidence: 91%
See 2 more Smart Citations
“…The frequency of FGFR2 mutations in this series (6.45%) is a little bit lower than that of previous series (10-12%). [13][14][15] However, the number of cases tested for FGFR2 mutations is smaller than that of other series. It is worth mentioning that our series has the additional value that the cases had been previously tested for microsatellite instability, as well as mutations of KRAS, PTEN, PIK3CA and CTNNB1.…”
Section: Fgfr2 Mutationsmentioning
confidence: 91%
“…Moreover, somatic mutations in the receptor tyrosine kinase FGFR2, identical to the germline mutations associated with craniosynostosis and skeletal dysplasia syndromes, have been recently detected in 10-12% of endometrial carcinomas, particularly in endometriod endometrial carcinomas (16%). [13][14][15] The somatic mutations included the S252W and P235R changes, which are associated with the Apert syndrome, the N549K and K659M, which are associated with Crouzon syndrome, as well as the N550K change. 31 Interestingly, FGFR2 and K-RAS FGFR2 in endometrial cancer mutations were mutually exclusive events, whereas mutations in FGFR2 and PTEN frequently coexisted.…”
Section: Fgfr2 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Several other studies indicated that FGFR2 is associated with carcinogenesis of some types of cancer; that is, overexpression or missense mutation of FGFR2 occurs in breast, lung, gastric and ovarian cancers. [10][11][12][13] However, the mechanism through which these intronic SNPs increase the risk of developing breast cancer remains unknown, although an association between these SNPs and reproductive hormones has been suspected by 2 epidemiological studies. 8,9 In the first study, a significant additive interaction between FGFR2 intronic polymorphisms and menopausal status was found in Chinese women, 8 and in the second study, a significant interaction between FGFR2 intronic polymorphisms and combined hormone replacement therapy use was found in European-American women.…”
Section: Uiccmentioning
confidence: 99%
“…Kinome exon sequencing in search of human cancer somatic mutations identifi ed FGF signaling components as the most frequently mutated coding regions among protein kinases ( 14 ). Somatic mutations of FGFR1 have been found in gliomas and lung tumors ( 15,16 ), of FGFR2 in gastric RESEARCH ARTICLE and endometrial carcinomas (17)(18)(19), of FGFR3 in bladder carcinomas and multiple myeloma ( 20,21 ), and of FGFR4 in primary rhabdomyosarcomas ( 22 ).…”
Section: Introductionmentioning
confidence: 99%